Tim Edwards (ed.), Cultural Theory (In Czech) - Juránková, Magda (Teorie vědy / Theory of Science, 2010)
Review: Tim EDWARDS (ed.), Kulturální teorie. Klasické a současné přístupy. Praha: Portál 2010, 368 s. (Cultural Theory. Classical and Contemporary Positions, 2007, přeložil David Vichnar).